Meningkatkan Aktivitas, Hasil Belajar Keterampilan Membaca Pemahaman Menggunakan Model Pelita pada Siswa Kelas IV - Muhammad Risal Herpindi; Dessy Dwitalia Sari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to address the issues of low student engagement, insufficient reading comprehension skills, and low learning outcomes in the fourth-grade class of SDN Juran Tabalong. These issues are attributed to the lack of student-centered teaching practices, monotonous and unengaging lessons, and suboptimal reading activities. Therefore, the proposed solution is to use a combined approach of the PELITA model in the teaching process. The objective of this research is to describe the teacher's activities and analyze the improvement of student engagement and the learning outcomes of reading comprehension skills. This research adopts the Classroom Action Research (CAR) method, conducted over four learning sessions in the fourth-grade class of SDN Juran Tabalong with the participation of 19 students. The data collected are analyzed through observations of both teacher and student activities, as well as the results of reading comprehension skills. Data analysis is carried out using a descriptive approach, and the results are presented in tables and graphs, then interpreted based on the predetermined criteria for each indicator of teacher activity, student activity, and the achievement of learning mastery in reading comprehension skills, both individually and as a group. The results of this research indicate that the teacher's activities implemented have received a score of 28, with an assessment of "excellent." Overall, the student activities in the class have also shown significant improvement, reaching 100% with an assessment of "very active." Furthermore, the students' reading comprehension skills have also experienced a notable increase, reaching 100% with an assessment of "very skillful." The cognitive learning outcomes of the students have improved overall, reaching 100% with an assessment of "mastery." The improvement in the affective learning outcomes of the students has reached 100% with the achievement of the mastery criteria. Likewise, the psychomotor learning outcomes have seen an increase of 100% with the attainment of the mastery criteria. Based on the findings of this research, it can be concluded that the use of the PELITA model is effective in enhancing students' reading comprehension skills in the fourth-grade class of SDN Juran Tabalong.